Correction: Evaluation of TNF-α, IL-10 and IL-6 Cytokine Production and Their Correlation with Genotype Variants amongst Tuberculosis Patients and Their Household Contacts. - PLOS ONE Editors (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0137727.].